1988
DOI: 10.1002/jcp.1041360304
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal proteins as the trigger for the induction of stress responses: Heat, diamide, and sodium arsenite

Abstract: Thermotolerance and synthesis of heat shock proteins are induced in cells in response to a variety of environmental stresses. We examined the suggestion of Hightower (1980) that modifications of intracellular proteins may be the triggering event that induces heat shock protein synthesis and thermotolerance. We did so by modifying cellular proteins, using diamide, a sulfhydryl oxidizing agent, and dithio-bis (succinimidyl propionate), an agent that cross-links bifunctional amino groups. Both of these agents ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 41 publications
4
44
0
Order By: Relevance
“…In the case of hHSF1, while it is clear that oxidation and intramolecular disulfide cross-link would stabilize the compact hHSF1 monomer and block its trimerization and activation, the effects of cysteine-SH oxidation in vivo are much more complex and likely involve multiple targets. For example, we observed that while diamide promoted the formation of ox-hHSF1 in HeLa cells, it also activated hHSF1, a result consistent with published observations (39,40). Furthermore, we showed in a previous study that thiol-reducing reagents inhibit the cellular heat shock response by blocking the activation, trimerization, and nuclear translocation of HSF1 (21).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the case of hHSF1, while it is clear that oxidation and intramolecular disulfide cross-link would stabilize the compact hHSF1 monomer and block its trimerization and activation, the effects of cysteine-SH oxidation in vivo are much more complex and likely involve multiple targets. For example, we observed that while diamide promoted the formation of ox-hHSF1 in HeLa cells, it also activated hHSF1, a result consistent with published observations (39,40). Furthermore, we showed in a previous study that thiol-reducing reagents inhibit the cellular heat shock response by blocking the activation, trimerization, and nuclear translocation of HSF1 (21).…”
Section: Discussionsupporting
confidence: 92%
“…However, these reagents (particularly diamide) caused activation of HSF1 DNA binding activity under a non-heat shock condition. In previous studies, diamide has been shown to induce the synthesis of heat shock proteins, presumably by producing oxidatively modified, abnormal proteins (39,40). This suggests that the effects of many of the oxidizing reagents in cells are complex due to their pleiotropic effect on the redox status of many cellular proteins.…”
Section: Figmentioning
confidence: 95%
“…When administered at non-lethal concentrations SA induces synthesis of a specific class of proteins, known as heat shock proteins (Hsps) and development of tolerance (Lee and Hahn, 1988;Nover, 1991;Welch, 1992). The phenomenon of SA-induced tolerance is described as a stress-induced cellular resistance to a lethal stress treatment (Wiegant et al, 1993).…”
Section: Inflammatory Bowel Diseases (Ibd) That Includementioning
confidence: 99%
“…Thus, the iron-mediated stress response seen in this study may be the result of free radical-mediated damage. Free radicals may induce a stress response by causing altered intracellular calcium concentrations (Keith et al, 1983;Lamarche et al, 1985), a lowering of intracellular pH (Weitzel et al, 1987;Nishimura et al, 1989), protein phosphorylation (Henle et al,I990), and production of abnormal proteins (Hightower, 1980;Ananthan et al, 1986;Lee and Hahn, 1988).…”
Section: Discussionmentioning
confidence: 99%